(untitled) (Al-Academy, 2025)
The researcher was interested in studying a useful topic for religious singing music, which is an artistic and cultural legacy of Iraqi society in general, and for religious and secular musical studies in the country in particular. He began searching for artistic figures whose productions had a clear impact on the religious singing musical culture in Iraq, specifying (Abdul Main Sunday) and its hymns that emerged at the beginning of the twentieth century in the Iraqi Chaldean Church and have continued to be circulated since their appearance until the time of preparing this research, influencing their recipients and being influenced by their surroundings and social and cultural environment. It was necessary to study its musical characteristics, including the structure of melody and rhythm, the two basic elements in the composition of popular traditional musical material, and this is what the research aimed to achieve. Therefore, the researcher developed the literature of his subject to serve the concepts related to church chanting and chanting and its performers from the church choir and others, in addition to clarifying the forms of religious chanting, and presenting their ancient reality and the events of renewal that occurred to them over the twentieth century through the concepts of openness and renewal. In the end, the researcher moves to the procedures in which he explained his community and his research sample, then adopts an analysis form that serves the goal of his research, and applies that form to two models that he subjected to analysis within his research sample, thus reviewing the results and conclusions he reached, which in turn achieved the desired goal of the research